Entrepreneurship in Portugal in relation to other European Union countries from 2010 to 2014: are we far from or close to the tipping point? - Santos, S. C. (2017)
This study analyses the dynamics of entrepreneurship in Portugal and other European Union countries from 2010 to 2014. We used the Global Entrepreneurship Monitor (GEM) data collected through representative samples of the population of each country to analyze three main areas: entrepreneurial activity, entrepreneurial attitudes and entrepreneurial aspirations. Our results show that in 2010, 2011, 2012 and 2013, the total early-entrepreneurship rate in Portugal was the same as the average in EU countries but in 2014 it was higher. However, this rise in entrepreneurial activity in Portugal in 2014 was mainly necessity-driven and not improvement-driven. The results also show that despite the fact that Portugal was perceived to have poor opportunities for new business during this period, Portuguese people believe more strongly than people in other countries that they have the required knowledge and skills to start a business. In general, although entrepreneurial attitudes in Portugal are characterized by average entrepreneurial intentions, lower perceived opportunities, higher perceived capabilities to start a business, their fear of failure would prevent them from starting a business. These results are relevant with regard to rethinking the promotion of entrepreneurship in Portugal.